Fiberconcrete with Non-Homogeneous Fibers Distribution (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In this research fiber reinforced concrete prisms with layers of non-homogeneous distribution of fibers inside them were elaborated. Fiber reinforced concrete is important material for load bearing structural elements. Traditionally fibers are homogeneously dispersed in a concrete. At the same time in many situations fiber reinforced concrete with homogeneously dispersed fibers is not optimal (majority of added fibers are not participating in load bearing process). It is possible to create constructions with non-homogeneous distribution of fibers in them in different ways. Present research is devoted to one of them. In the present research three different types of layered prisms with the same amount of fibers in them were experimentally produced (of this research prisms of non-homogeneous fiber reinforced concrete with dimensions 100×100×400 mm were designed. and prisms with homogeneously dispersed fibers were produced for reference as well). Prisms were tested under four point bending conditions till crack opening in each prism reached 6 mm.  During the testing vertical deflection at the center of a prism and crack opening were fixed by the linear displacements transducers in real time.